Selective C-H Activation at a Molecular Rhodium Sigma-Alkane Complex by Solid/Gas Single-Crystal to Single-Crystal H/D Exchange - Chadwick, F; Krämer, T; Gutmann, T; Rees, N; Thompson, A; Edwards, A; Buntkowsky, G; Macgregor, S; Weller, A (American Chemical Society, 2016)
The controlled catalytic functionalization of alkanes via the activation of C-H bonds is a significant challenge. Although C-H activation by transition metal catalysts is often suggested to operate via intermediate σ-alkane complexes, such transient species are difficult to observe due to their instability in solution. This instability may be controlled by use of solid/gas synthesis techniques that enable the isolation of single-crystals of well-defined σ-alkane complexes. Here we show that using this unique platform, selective alkane C-H activation occurs, as probed by H/D exchange using D2, and that five different isotopomers/isotopologues of the σ-alkane complex result, as characterized by single-crystal neutron diffraction studies for three examples. Low-energy fluxional processes associated with the σ-alkane ligand are identified using variable-temperature X-ray diffraction, solid-state NMR spectroscopy and periodic DFT calculations. These observations connect σ-alkane complexes with their C-H activated products, and demonstrate that alkane-ligand mobility, and selective C-H activation, are possible when these processes occur in the constrained environment of the solid-state.